Hypoxia induced EMT: A review on the mechanism of tumor progression and metastasis in OSCC. (May 2018) - Joseph, Joel P.; Harishankar, M.K.; Pillai, Aruthra Arumugam; Devi, Arikketh
Highlights: The role of hypoxia and the associated factors (HIF) in tumor progression and metastasis. The oncogenic pathways involved in tumor progression and metastasis in OSCC. A complete picture of how HIFs induce EMT through oncogenic pathways. Therapeutic perspectives. Abstract: Hypoxia, a condition of low oxygen tension in tissues, has emerged as a crucial factor in tumor pathophysiology. Hypoxic microenvironment gives rise to altered cellular metabolism and triggers varied molecular responses. These responses promote tumor progression and confer radiation resistance and chemo resistance to tumors. The predominant molecules that are associated with hypoxia research are the hypoxia inducible factors (HIFs). HIFs are known to regulate a large group of genes that are involved in cell survival, proliferation, motility, metabolism, pH regulation, extracellular matrix function, inflammatory cell recruitment and angiogenesis by inducing the expression of their downstream target genes. The process of epithelial to mesenchymal transition (EMT) has been associated with metastasis in cancer. Reports also suggest that hypoxia triggers EMT in several types of cancer including breast cancer, prostate cancer and oral cancer. Oral cancer is a predominant cancer in Central and South East Asia. However, in the recent times, the incidence rates of oral cancer have been increasing in Northern and Eastern Europe as well. This review articulates the role of hypoxia and the associated factors like HIFs in inducing EMT in oral cancer (OSCC).